An Analysis on Students’ Ability in Using Compound-Complex Sentences in Writing a Short Essay - A Afri Rahma; Rusdi Noor Rosa (Journal of English Language Teaching, 2021)
The purpose of the research is to figure out the students’ ability in constructing compound-complex sentence in essays writing. The design used in this research is descriptive research with second year students of English language educational program of UNP as the research population. There were 30 students taken as the sample selected by using cluster sampling technique in K5-2018 class. The data were collected through documents of students’ essay writing. The essays were analyzed by the researcher, and it was revised by a valuator and two raters as the validity and reliability of this research. They are the lecturers of English department at UniversitasNegeri Padang. The finding shows that the ability of students in writing compound-complex sentence is in the level of good with the average percentage 79.18%. Most students generally can make compound-complex sentences in their essays writing, but they have problems in: 1) incorrect use of punctuation, especially comma, 2) lacks a subject or a verb in the compound-complex sentence. Therefore, an intensive attention should be given by the lecturer to facilitate the students to practice both writing and grammar by using peer correction.